Do Family Proxies Get It Right? Concordance in Reports of Nursing Home Residents' Everyday Preferences. (June 2017) - Heid, Allison R.; Bangerter, Lauren R.; Abbott, Katherine M.; Van Haitsma, Kimberly
Limited work has examined how well family proxies understand nursing home residents' preferences. With 85 dyads of a nursing home resident and relative, we utilize descriptive statistics and multi-level modeling to examine the concordance in reports of importance ratings of 72 everyday preferences for residents. Results reveal significant mean differences at the p < .001 level between proxies and residents on 12 of 72 preferences; yet, perfect agreement in responses is poor and only increases when dichotomizing responses into an important versus not important outcome. Multi-level modeling further indicates that dyads are discrepant on reports of the importance of growth activities for residents, with residents reporting higher levels of importance than proxies. This discrepancy is associated with residents' hearing impairment and proxies' perception of resident openness. The findings highlight not only how proxies may be able to inform care for residents in nursing homes but also where further discussions are warranted.